2021
DOI: 10.1186/s12872-021-02112-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of nicorandil on isoproterenol induced cardiomyopathy in the Mdx mouse model

Abstract: Background Duchenne muscular dystrophy (DMD) associated cardiomyopathy is a major cause of morbidity and mortality. In an in vitro DMD cardiomyocyte model, nicorandil reversed stress-induced cell injury through multiple pathways implicated in DMD. We aimed to test the efficacy of nicorandil on the progression of cardiomyopathy in mdx mice following a 10-day treatment protocol. Methods A subset of mdx mice was subjected to low-dose isoproterenol inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…58,64,65 Our lab has previously modeled DMD cardiomyopathy using low dose isoproterenol to induce cardiac injury and found this model sufficiently unmasks the cardiac defect present in young mdx but not WT mice. 15 Recently, we examined the effects of short-term nicorandil treatment on isoproterenol-induced cardiac injury in young mdx mice. 15 This short-term study demonstrated that nicorandil treatment in young mdx mice rescued isoproterenol-induced cardiac injury through improving % EF and FS, diminishing cardiac fibrosis and enhancing antioxidant levels (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…58,64,65 Our lab has previously modeled DMD cardiomyopathy using low dose isoproterenol to induce cardiac injury and found this model sufficiently unmasks the cardiac defect present in young mdx but not WT mice. 15 Recently, we examined the effects of short-term nicorandil treatment on isoproterenol-induced cardiac injury in young mdx mice. 15 This short-term study demonstrated that nicorandil treatment in young mdx mice rescued isoproterenol-induced cardiac injury through improving % EF and FS, diminishing cardiac fibrosis and enhancing antioxidant levels (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, we examined the effects of short-term nicorandil treatment on isoproterenol-induced cardiac injury in young mdx mice. 15 This short-term study demonstrated that nicorandil treatment in young mdx mice rescued isoproterenol-induced cardiac injury through improving % EF and FS, diminishing cardiac fibrosis and enhancing antioxidant levels (Table 3). That study served as the rationale for us to examine whether long-term nicorandil treatment could also be cardioprotective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations